Male blue monkeys alarm call in response to danger experienced by others - Papworth, Sarah; Böse, Anne-Sophie; Barker, Jessica; Schel, Anne Marijke; Zuberbühler, Klaus (My University, 2008)
Male blue monkeys (Cercopithecus mitis stuhlmanni) of Budongo Forest, Uganda, produce two acoustically distinct alarm calls: hacks to crowned eagles (Stephanoaetus coronatus) and pyows to leopards (Panthera pardus) and a range of other disturbances. In playback experiments, males responded to leopard growls exclusively with a series of pyows and to eagle shrieks predominantly with hacks. Responses to playbacks of these alarm call series matched the responses to the corresponding predators, suggesting that the calls conveyed something about the nature of the threat. When responding to a series of hacks, indicating an eagle, males responded predominately with hacks, but produced significantly more calls if their group members were close to the playback stimulus than far away, regardless of their own position. When responding to a series of pyows, indicating a range of disturbances, males responded with pyows, but call rates were independent of the distance of other group members. The results suggest that males took into account the degree of danger experienced by other group members.
Keywords: audience effect; vocal behaviour; predation; Cercopithecus; alarm call; referential